Magnetic susceptibility mapping of the Cambrian El Hongo pluton, Eastern Sierras Pampeanas, Argentina - Geuna, Silvana Evangelina (2017)
A map of bulk magnetic susceptibility was obtained on El Hongo trondhjemite, a small Cambrian pluton intruding the metamorphic basement in Eastern Sierras Pampeanas, Argentina, based on systematic magnetic susceptibility measurement at 450 sites using a SM30 susceptibility meter. Samples were collected on 58 sites and their bulk magnetic susceptibility was measured in laboratory with a Bartington MS2 system. Point-to-point comparison showed differences, that were attributed to the effect of roughness of the surveyed surfaces, and to the development of a weathered cap. However, the difference was systematic and in accordance with expected values predicted by manufacturer tables, whereby, once corrected with the appropriate factor, the obtained values with SM30 susceptibility meter were regarded as representative of fresh rocks. The resulting map was interpreted in terms of variation in abundance of magnetite, which is present in the rocks as a magmatic mineral, altered to hematite (martitized) in varying degrees. The map revealed that El Hongo trondhjemite is a weakly magnetic pluton, with a typical bulk susceptibility of about 500 × 10−6 SI, which would correspond to an abundance of magnetite below 0.2 vol%, but with conspicuous variations. Lows in the outer sector and in the vicinity of metamorphic xenoliths were interpreted as due to destruction of magnetic minerals linked to reactions between magma and host rock. A distinct concentric pattern in the western area could indicate the presence of a separate intrusion. Finally, alternate highs and lows in susceptibility follow the undulations in regional schistosity, which in turn would have controlled the emplacement of the pluton. Thus we provide a good example of the utility of magnetic susceptibility mapping in granitoid terrains, as an expeditious way for preliminary mapping that could guide further and more detailed research.